Head-stem trunnion dissociation due to corrosion in total hip arthroplasty - Whitehouse, Michael R. (Annals of Translational Medicine; Vol 5, No 17 (September 15, 2017): Annals of Translational Medicine, 2017)
The use of modularity in implant design in orthopaedics is extremely common, particularly in areas such as total hip arthroplasty (1). It has the advantages of allowing the surgeon to carefully select the perceived correct combination of implants in order to restore the biomechanics of the hip joint, principally leg length and offset. The use of modularity allows a much-reduced inventory of implants in comparison to having all combinations available as monoblock implants. Modularity also provides advantages in the revision situation, such as the ability to perform a debridement with implant retention and modular exchange for infection, ease of access to the acetabular component to facilitate revision and the ability to retain a well-fixed stem in other indications for revision.